The role and status of learner’s dictionaries in efl education: theoretical foundations and future perspectives - Bytko, Nataliya; Битко, Наталія Сергіївна (Запоріжжя : 2025, 2025)
EN: This paper explores the evolving role of learner’s dictionaries in English as a Foreign Language (EFL) education. Re-examining their theoretical foundations, typology, and current applications, it highlights their pedagogical value in vocabulary development, grammar awareness, and learner autonomy. A mixed-methods approach – including theoretical, corpus-based, and comparative analyses – is proposed to assess printed and digital formats, emphasizing the need for context-specific, user-oriented works in modern language learning environments.
Keywords: learner’s dictionaries; English language education; lexicographic typology; vocabulary acquisition